Factors Affecting Health Workers’ Self Efficacy in Dealing with Earthquake and Tsunami Disasters - Sanjaya, Waqid; Budhiana, Johan; Ida, Ida (GLOBAL HEALTH SCIENCE GROUP, 2025)
Indonesia is located along a mountainous circumference and on the equator. This topographical situation makes Indonesia a disaster-prone area, which has the potential to cause losses. Health workers have an important role in disaster preparedness, but their level of self-efficacy in dealing with disasters such as earthquakes and tsunamis can be influenced by various factors. Objective: The purpose of this study was to determine the factors that influence self-efficacy in health workers in facing earthquake and tsunami disasters. Methods: This type of research is correlational with a cross sectional approach. The population was all health workers in the Puskesmas of Sukabumi Regency Coastal Area, 512 people and a sample of 200 people using proportional random sampling. Data collection using questionnaires. Data analysis used univariate analysis with frequency distribution, bivariate analysis with Chi-Square correlation, and multivariate analysis with binary logistic regression. Results: The results showed that there was an effect of age (0.000), gender (0.000), education (0.000), marital status (0.000) and having experienced a disaster (0.000) on the self-efficacy of health workers in dealing with disasters. Conclusion: There is an influence of age, gender education, marital status, and having experienced a disaster on the self efficacy of health workers in dealing with disasters.